Add-On Effects of Chinese Herbal Medicine for Post-Stroke Spasticity: A Systematic Review and Meta-Analysis - Yiyi Cai; Yiyi Cai; Claire Shuiqing Zhang; Shaonan Liu; Zehuai Wen; Anthony Lin Zhang; Xinfeng Guo; Charlie Changli Xue; Charlie Changli Xue; Chuanjian Lu; Chuanjian Lu (Frontiers Media S.A., 2019)
Background: Treatment for post-stroke spasticity (PSS) remains a major challenge in clinical practice. Chinese herbal medicine (CHM) is often administered to assist in routine care (RC) in the treatment of PSS, with increasing numbers of clinical research and preclinical studies suggesting that it has potential benefits. Therefore, we conducted a systematic review and meta-analysis to evaluate the add-on effects and safety of CHM for PSS.Methods: Five English and four Chinese databases were searched from their respective inception to 28 February 2018. We included randomized controlled trials that evaluated the add-on effects of CHM for PSS, based on changes in the scores of the (Modified) Ashworth Scale (AS or MAS), Fugl-Meyer Assessment of Sensorimotor Recovery (FMA), and Barthel Index (BI).Results: Thirty-five trials involving 2,457 patients were included. For upper-limb AS or MAS, the estimated add-on effects of CHM to RC were significantly better when using oral (SMD −1.79, 95% CI: −3.00 to −0.57) or topical CHM (SMD −1.06, 95% CI: −1.40 to −0.72). For lower-limb AS or MAS, significant add-on benefits to RC were also detected (SMD −1.01, 95% CI: −1.43 to −0.59 and SMD −1.16, 95% CI: −1.83 to −0.49) using oral and topical CHM, respectively. For FMA and BI, better results were detected when adding CHM to RC, except for the subgroup of oral CHM for upper-limb FMA. Ten of the 35 included studies reported safety information, with two of them mentioning two mild adverse events.Conclusions: Noting the quality concerns of the included trials, this review suggests that CHM appears to be a well-tolerated therapy for patients with PSS, and the potential add-on effects of CHM in reducing spasticity and improving the daily activities of patients with PSS require further rigorous assessment.